Cote d'Ivoire : Poverty Reduction Strategy Paper-Joint Staff Advisory Note. (IMF Staff Country Reports; Country Report ;, 2013)
The NDP aims at transforming Cote d'Ivoire into an emerging market and halving the poverty rate. The framework for poverty reduction can be improved by developing a program of targeted interventions to support growth in key strategic sectors, public investment management, maintaining fiscal and debt sustainability and implementation of energy sector reforms. The fiscal strategy focuses on scaling up public investment and sustainability. The public sector investment program and the macroeconomic projections of the PND are a good strategy. Risks to successful implementation are exogenous shocks, resistance to structural reforms, and sociopolitical instability in the country.